Анализа корелације нивоа серума NT-прo-BNP, IGFBP-7 и CTRP12 код пацијената са хроничном срчаном инсуфицијенцијом: Нивои серума NT-прo-BNP, ИГФБП-7 и ЦТРП12 код хроничне срчане инсуфицијенције - Fan, Zhen; Huang, Heng; Hua, Hejuan; Chen, Lin; Wang, Laoji; Yan, Jierou; Zhao, Fei (Journal of Medical Biochemistry, 2025)
Objective: To investigate serum N-terminal pro-brain natriuretic peptide (NT-pro-BNP), insulin-like growth factor binding protein-7 (IGFBP-7), and C1q tumor necrosis factor-related protein 12 (CTRP12) levels and significance in patients with chronic heart failure (CHF). Methods: The CHF group consisted of 116 CHF patients who received care at this hospital between October 2023 and March 2025. The patients were classified into Grade II (47 patients), Grade III (41 patients), or Grade IV (28 patients) based on the heart function classification of the New York Heart Association (NYHA). The control group consisted of 64 healthy patients who were examined physically in the hospital throughout the same time period. Using multivariate logistic regression, the factors impacting MACEs in patients with congestive heart failure were examined. Through the use of the receiver operating characteristic (ROC) curve, researchers were able to assess the predictive power of blood NT-pro-BNP, IGFBP-7, and CTRP12 for MACEs in chronic heart failure patients. Results: Comparing the CHF group to the control group, the LVEDD increased, the LVEF and serum CTRP12 decreased, and the levels of NT-pro-BNP, IGFBP-7, Hcy, and hs-CRP climbed (P<0.05). Among patients with CHF of different grades, serum NT-pro-BNP, IGFBP-7, Hcy, hs-CRP, and LVEDD levels were all lower in Grade II patients than in Grade III patients. Furthermore, the differences between any two grades were statistically significant (P<0.05). The levels of LVEF and serum CTRP12 in the MACE group decreased, the LVEDD increased, and the levels of serum Hcy, hs-CRP, NT-pro-BNP and IGFBP-7 increased (P<0.05). MACEs in CHF patients were influenced by serum NT-pro-BNP, IGFBP-7, and CTRP12 (P<0.05). The areas under the curve (AUCs) of serum NT-pro-BNP, IGFBP-7, CTRP12 alone and the combination of the three for predicting MACEs in patients with CHF were 0.862 (95% CI: 0.786–0.919), 0.805 (95% CI: 0.721–0.872), and 0.860 (95% CI: 0.784–0.918) and 0.961 (95% CI: 0.908–0.988), respectively. The AUCs of the three combined predictions were significantly greater than those of the individual predictions of NT-pro-BNP, IGFBP-7, and CTRP12 (Z=3.050, 3.883, 3.218, all P<0.05). Conclusion: Serum levels of IGFBP-7 and NT-pro-BNP increase in CHF patients, whereas the level of CTRP12 decreases. Additionally, once functional classification was applied, NT-pro-BNP, IGFBP-7, and CTRP12 levels changed. The combined detection of these three parameters has better efficacy in predicting MACEs in patients with CHF.